Technical Guidance for Making Budget Plans in Kedungrejo Village, Rembang Regency - Hendra Masvika; Hani Purwanti (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
In building a village infrastructure, it is necessary to calculate the costs contained in the Budget Plan (RAB) according to the standards set by the government. The RAB provides an overview of the costs required to construct a structure or building. In addition, from the calculation of the RAB, it can also be seen that the building material requirements, manpower, and the schedule needed to complete the project. The purpose of this technical guidance is to increase the role and understanding of village officers and youth organizations in making RAB. Technical guidance is carried out by providing explanations and technical assistance directly to partners in making the RAB for the physical infrastructure project for the concrete pavement access to the mosque. The results of the technical guidance showed that there was an increase in the understanding of partners in making RAB by 70%. In addition, 50% of partners believe that they can independently make RAB for a similar project. Armed with this understanding, it is hoped that in the future partners can play a greater role in the village's physical development process starting at the planning, construction, and supervision stages of the project.